Intentional music use to reduce psychological distress in adolescents accessing primary mental health care. (October 2018) - McFerran, Katrina Skewes; Hense, Cherry; Koike, Asami; Rickwood, Debra
Rationale: Many young people turn to music as a way of exploring and managing their moods and emotions. The literature is replete with studies that correlate music preferences and mental health, as well as a small but increasing interest in uses of music to promote well-being. Recent studies have shown that music use is often unconscious, thus difficult to influence without therapeutic conversations. No study has yet tested whether it is feasible to increase awareness of music use in young people who tend to ruminate with music, and test whether increased awareness can reduce distress. Design: This feasibility study aimed to determine whether involvement in a brief music-based intervention was engaging and acceptable to a small sample of young people, and whether their levels of distress decreased and insight into music uses increased. A mixed methods approach was adopted, merging scores of distress and self-reported experience of the intervention to foster interpretation. Results: Convergent analysis of the different data forms suggests that at least some of the measurable decreases in distress captured for all of the participants were related to participation in the sessions, according to the self-report of a number of the young people in interviews. This is demonstrated through descriptive data compiled under two key themes (Agency and Changed Uses) and illustrated through three case examples that were drawn largely from the words of the young people. Conclusion: This feasibility study suggests that young people's relationship with music provides a powerful platform for leveraging engagement in services and improvements in distress, when well timed and carefully scaffolded.